TASK-BASED LEARNING AS AN EFFECTIVE TEACHING METHOD - Mamanazarova Rayhona Nurbek qizi, (TADQIQOTLAR, 2025)
Abstract: Task-Based Learning (TBL) is one of the most influential approaches in modern language education, emphasizing learning through meaningful tasks rather than isolated grammar exercises. This method encourages students to communicate, collaborate, and think critically while using the target language in authentic situations. It develops both linguistic competence and communicative performance. The present paper  explores  the  theoretical  foundation,  principles,  and  practical  implications  of TBL, highlighting its effectiveness in fostering learner autonomy and communicative fluency.